Amphetamine derivatives and obesity - Ricca, Valdo; Castellini, Giovanni; Mannucci, Edoardo; Monami, Matteo; Ravaldi, Claudia; Gorini Amedei, Silvia; Sauro, Carolina Lo; Rotella, Carlo Maria; Faravelli, Carlo (Appetite, 2009)
This study aims to investigate the anamnestic, psychopatological and clinical features of overweight/obese subjects with and without an history of amphetamine derivatives consumption. This survey was conducted on a consecutive series of 451 overweight/obese subjects referring to the Clinics for Obesity of the University of Florence. Subjects with and without previous amphetamines derivatives consumptions were compared in terms of psychopathological and clinical features by means of the Structured Clinical Interview for DSM-IV, the Eating Disorder Examination questionnaire (EDE-Q), the Binge Eating Scale (BES), the Beck Depression Inventory (BDI), and the Spielberg's State-Trait Anxiety Inventory (STAI). Among the 451 participants, 136 patients (30.1%) reported a previous use of amphetamine derivatives drugs. Amphetamine users reported a high rate of childhood overweight, and showed higher BMI, EDE-Q Total score, Weight Concern, Shape Concern subscales and BES scores than amphetamine non-users, whereas the two groups of patients did not differ in terms of BDI and STAI scores. Amphetamine derivatives are widely used by obese patients seeking weight loss treatment. The amphetamine derivatives consumption is associated with higher levels of eating psychopathology and a more severe overweight.